Implementation of Internet of Things Appropriate Technology as River Mitigation in Tubing Tourism - Sudianto Sudianto; Reni Dyah Wahyuningrum (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
The purpose of this activity is the application of Internet of Things (IoT)-based Appropriate Technology (TTG) for the establishment and mitigation of sustainable river tubing tourism on the Pelus Karanggitung river, Banyumas. This activity is carried out as mitigation and warning for the river system at tourist locations. The method used in this activity is the installation of appropriate technology tools for the Internet of Things and assistance. The output target of this activity is to install appropriate technology such as a warning and mitigation system at tourist attractions. In addition, it is hoped that the continuation of this activity will make the Pelus Tubing Tour run and have a warning system for river mitigation. Based on the results of the activity, it can be concluded that this activity is in accordance with the needs of partners, because it can prevent unexpected events from river water at tubing tourism sites. Apart from that, this activity can increase partners' awareness of the river environment.